Philippines : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Philippines. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that the economy of The Philippines continues to perform well but is facing new challenges. Real GDP growth is projected to grow strongly in 2018 and 2019, supported by domestic demand. However, poverty and inequality challenges remain, inflation has risen, and external uncertainty has increased. The medium-term economic outlook remains favorable, but short-term risks have risen. Real GDP growth is projected at just under 7 percent over the medium term. Inflation is projected at above the 4 percent upper target bound in 2018 and stay in the upper half of the target band during 2019-2020. The current account deficit is projected to remain manageable, financed largely by foreign direct investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet